Substructure in Raub biomass power plant / Ahmad Fikri Saipuzzaman - Saipuzzaman, Ahmad Fikri Saipuzzaman (Universiti Teknologi MARA, Perak, 2018)
The substructure is defined as the structural work below ground level used to support the structure above. Foundations, basement, subfloor are some components of this area. (www.gcon.ie). There are two types of foundation which are shallow foundation and deep foundation. Shallow foundations are typically used where the loads imposed by a structure are low relative to the bearing capacity of the surface soils. Deep foundations are necessary where the bearing capacity of the surface soils is not adequate to support the loads imposed by a structure and so those loads need to be transferred to deeper layers with higher bearing capacity.